2019
DOI: 10.1039/c8me00080h
|View full text |Cite
|
Sign up to set email alerts
|

Role of antibody heavy and light chain interface residues in affinity maturation of binding to HIV envelope glycoprotein

Abstract: Optimization of the heavy chain/light chain interface could serve as an important tool for maximizing antibody/antigen binding affinity without altering antigen contact residues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…As noted in section 3.1, the mutant position L-K45 is a solvent accessible residue while L-Q48 is responsible for forming polar contacts with the heavy chain. The performance of these mutants a rms the importance of mutations at the heavy and light chain interface in improving binding a nity speci city as also shown by Cisneros and colleagues [29].…”
Section: Discussion and Conclusion 41 Mutationssupporting
confidence: 55%
“…As noted in section 3.1, the mutant position L-K45 is a solvent accessible residue while L-Q48 is responsible for forming polar contacts with the heavy chain. The performance of these mutants a rms the importance of mutations at the heavy and light chain interface in improving binding a nity speci city as also shown by Cisneros and colleagues [29].…”
Section: Discussion and Conclusion 41 Mutationssupporting
confidence: 55%
“…First, we confirmed that the anti-NET immunoreactivity was completely lost in the GL counterpart whereas the anti-cit-H2B immunoreactivity was reduced by over 60%. Recent studies have shown that SHM in the HC/LC interface, distant from the region of contact between Ag/Ab, play an important role in the highaffinity recognition of the Ag (15). Moreover, it was recently proposed that SHM could generate new reactivity and/or polyreactivity toward cit-Ags, causing epitope spreading in the ACPA response (16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
“…This modulation of chain interface relationships has been investigated recently by Cisneros et al, who found VH–VL interface residues were reverted to the germline sequence, which resulted in significant loss of affinity, and indicated that the rigidification of the VH–VL interface, which will determine its orientation, is a major driver for affinity maturation. 61 RosettaAntibody selects 10 different framework matches as starting structures for loop grafting. The selected template loops are superimposed on the framework based on two overlapping residues and optimized through a cycle of minimizations, random torsional sampling and cyclic coordinate descent (CCD).…”
Section: Methods For Antibody Structure Prediction and Designmentioning
confidence: 99%